Relationship between B‐cell epitope structural properties and the immunogenicity of blood group antigens: Outlier properties of the Kell K1 antigen. Issue 11 (7th October 2022) - Howe, John G.; Stack, Gary
Abstract: Background: The immunogenicities of polypeptide blood group antigens vary, despite most being created by single amino acid (AA) substitutions. To study the basis of these differences, we employed an immunoinformatics approach to determine whether AA substitution sites of blood group antigens have structural features typical of B‐cell epitopes and whether the extent of B‐cell epitope properties is positively related to immunogenicity. Study design and methods: Fifteen structural property prediction programs were used to determine the likelihood of β‐turns, surface accessibility, flexibility, hydrophilicity, particular AA composition and AA pairs, and other B‐cell epitope properties at AA substitution sites of polypeptide blood group antigens. Results: AA substitution sites of Lu a, Jk a, E, c, M, Fy a, C, and S were each located in regions with at least two structural features typical of B‐cell epitopes. The substitution site of K, the most immunogenic non‐ABO/D antigen, scored the lowest for most B‐cell epitope properties and was the only one not predicted to be part of a linear B‐cell epitope. The most immunogenic antigens studied (K, Jk a, Lu a, E) had B‐cell epitope structural properties determined by the fewest programs; the least immunogenic antigens (e.g., Fy a, S, C, c) had B‐cell epitope properties according to the most programs. Discussion: Counter to prediction, the immunogenicity of polypeptide blood group antigens was not positively related to B‐cell epitope structural features present at their AA‐substitution sites. Instead, it tended to be negatively related. The AA‐substitution site of the most immunogenic non‐ABO/D antigen, K, had the least B‐cell epitope features.